2016
DOI: 10.1097/md.0000000000002190
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Model for Stage II Colon Cancer Patients With Nonemergent Surgery

Abstract: No ideal prognostic model has been applied to clearly identify which suitable high-risk stage II colon cancer patients with negative margins undergoing nonemergent surgery should receive adjuvant chemotherapy routinely.Clinicopathologic and prognostic data of 333 stage II colon cancer patients who underwent D2 or D3 lymphadenectomy during nonemergent surgery were retrospectively analyzed.Four pathologically determined factors, including adjacent organ involvement (RR 2.831, P = 0.001), histologic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…So, the percentage of lymphovascular invasion in SRCC is higher than conventional adenocarcinoma. Some articles have already reported that lymphovascular invasion was a prognostic variable in conventional adenocarcinoma[ 27 , 28 ]. Since lymphovascular invasion means invasion of tumor cells into lymph or blood vessels, which is important in metastatic process, and SRCC has a high rate of metastasis, we have reasons to believe that lymphovascular invasion can be a good factor for predicting prognosis in colorectal SRCC.…”
Section: Discussionmentioning
confidence: 99%
“…So, the percentage of lymphovascular invasion in SRCC is higher than conventional adenocarcinoma. Some articles have already reported that lymphovascular invasion was a prognostic variable in conventional adenocarcinoma[ 27 , 28 ]. Since lymphovascular invasion means invasion of tumor cells into lymph or blood vessels, which is important in metastatic process, and SRCC has a high rate of metastasis, we have reasons to believe that lymphovascular invasion can be a good factor for predicting prognosis in colorectal SRCC.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, different clinicopathologic features, such as T4 tumor, low count lymph node evaluation, high-grade tumor, male gender, bowel obstruction, presence of LVI or PNI, and high preoperative CEA, have been linked to a high possibility of death and recurrence (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study evaluated the use of multiple markers to improve the ability to identity high-risk stage II colon cancer patients (35). They used 4 pathology-determined parameters: adjacent organ involvement, histological differentiation, lymphovascular invasion and the number of lymph nodes retrieved.…”
Section: Discussionmentioning
confidence: 99%